Battery Model Parameters Estimation Using Simulated Annealing - Brondani, Marcia de Fatima; Sausen, Airam Teresa Zago Romcy; Sausen, Paulo Sérgio; Binelo, Manuel Osório (Trends in Computational and Applied Mathematics, 2017)
In this paper, a Simulated Annealing (SA) algorithm is proposed for the Battery model parametrization, which is used for the mathematical modeling of the Lithium Ion Polymer (LiPo) batteries lifetime. Experimental data obtained by a testbed were used for model parametrization and validation. The proposed SA algorithm is compared to the traditional parametrization methodology that consists in the visual analysis of discharge curves, and from the results obtained, it is possible to see the model efficacy in batteries lifetime prediction, and the proposed SA algorithm efficiency in the parameters estimation.